The role of surgery in advanced thymic tumors: A retrospective cohort study - Weifeng Qi; Hui Tian (Frontiers in Oncology, 2023)
BackgroundThere is no definitive and detailed treatment guideline for advanced thymic tumors, thus when lymph node and other organ metastasis are present, clinical guidelines recommend chemotherapy-based multidisciplinary treatment. A consensus has been reached that surgery has beneficial effects on partial patients with stage IVA whose metastatic lesions were isolated and resectable, but because of few cases of advanced thymic tumor s and the scarcity of reports, the role of surgery in stage IVB is still unknown. The current study aimed to systematically analyze the role of surgery in advanced thymic tumors based on the Surveillance, Epidemiology, and End Results (SEER) database, with a sufficient number of cases. A secondary aim was to clarify the prognostic value of surgery in advanced thymic tumors.MethodData derived from a total of 979 patients with advanced thymoma or advanced thymic carcinoma were collected from the SEER database. Propensity score matching was performed to eliminate confounding factors, and Cox regression analyses were conducted to assess prognoses.ResultsPatients were assigned to four groups based on pathology and whether surgery was performed; thymoma (surgery), thymoma (no surgery), thymic carcinom a (surgery), and thymic carcinoma (no surgery). Disease-specific survival differed significantly in the thymoma (surgery) and thymoma (no surgery) groups, both before and after propensity score matching (both p < 0.001). Similarly, disease-specific survival differed significantly in the thymic carcinoma (surgery) and the thymic carcinoma (no surgery) groups (p < 0.001 before and p = 0.003 after). No total resection, distant metastasis, and thymic carcinoma were all unfavorable prognostic factors.ConclusionsIn the present study surgery had positive effects on advanced thymoma and advanced thymic carcinoma patients who could undergo surgical resection, significantly improving survival times. Total resection of the primary site was the most advantageous form of surgery. The study provides a reference for the clinical treatment of advanced thymic tumors.